2018
DOI: 10.21037/tau.2018.07.19
|View full text |Cite
|
Sign up to set email alerts
|

Assessing lymph node status in patients with kidney cancer

Abstract: Accurate detection of lymph node involvement on pre-operative imaging in patients diagnosed with renal cell carcinoma (RCC) is critical for determination of disease stage, one of the most significant prognostic factors in RCC. The presence of lymph node involvement in RCC doubles a patient’s risk of distant metastasis and significantly reduces their 5-year survival. Currently, lymph node involvement in patients with RCC is evaluated with numerous modalities, with rapid advancements occurring across these modal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 31 publications
1
18
0
Order By: Relevance
“…Additionally, the influence of regional lymph node involvement on the distant metastatic potential of RCC was also demonstrated in our finding. Another study found that regional lymph node involvement increased the occurrence of distant metastasis by 50% (44). Our nomogram highlighted the fact that the rate of distant metastasis increased with the RCC differentiation (from well to poorly differentiated).…”
Section: Discussionsupporting
confidence: 58%
“…Additionally, the influence of regional lymph node involvement on the distant metastatic potential of RCC was also demonstrated in our finding. Another study found that regional lymph node involvement increased the occurrence of distant metastasis by 50% (44). Our nomogram highlighted the fact that the rate of distant metastasis increased with the RCC differentiation (from well to poorly differentiated).…”
Section: Discussionsupporting
confidence: 58%
“…In addition, we found that the proportion of all metastatic patterns showed stable trends with no obvious changes in recent years. However, the metastatic rate in this study was significantly lower than 18%–30% reported in previous studies 6,7 . We attributed this to the fact that we only included patients with distant organs metastases, while regional (did not meet the inclusion criteria) and distant (due to the limitation of the database itself) lymph node metastases (LNM) were excluded.…”
Section: Discussionmentioning
confidence: 61%
“…However, the metastatic rate in this study was significantly lower than 18%-30% reported in previous studies. 6,7 We attributed this to the fact that we only included patients with distant organs metastases, while regional (did not meet the inclusion criteria) and distant (due to the limitation of the database itself) lymph node metastases (LNM) were excluded. Moreover, only ccRCC was included in this study, while some other pathological types had high potential for malignant metastasis, such as Bellini duct carcinoma and medullary carcinoma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A longer TNM stage progression results in a lower 5-year survival rate in patients diagnosed with renal cell carcinoma [ 36 ]. CRBN expression in nodal metastasis level N1 (i.e., metastasis in one to three axillary lymph nodes) was lower than in N0 (i.e., no regional lymph node metastasis), as illustrated in Figure 3 g [ 37 ]. Based on the KIRC subtype, the ccA subtype overexpresses a set of genes involved in hypoxia, angiogenesis, fatty acid metabolism, and organic acid metabolism, whereas the ccB subtype overexpresses genes involved in cell differentiation, epithelial to mesenchymal transition (EMT), cell cycle, and transforming growth factor beta (TGFβ), resulting in a more aggressive cancer progression [ 38 ].…”
Section: Discussionmentioning
confidence: 99%